Ant Colony Optimization for Real Time Traffic Lights Control on a Single Intersection - Rida, Nouha; Ouadoud, Mohammed; Hasbi, Aberrahim (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In this paper, we present a new scheme to intelligently control the cycles and phases of traffic lights by exploiting the road traffic data collected by a wireless sensor network installed on the road. The traffic light controller determines the next phase of traffic lights by applying the Ant Colony Optimazation metaheuristics to the information collected by WSN. The objective of this system is to find an optimal solution that gives the best possible results in terms of reducing the waiting time of vehicles and maximizing the flow crossing the intersection during the green light. The results of simulations by the SUMO traffic simulator confirm the preference of the developed algorithm over the predefined time controller and other dynamic controllers.